Survey the Occurrence of Globocephalus urosubulatus (Nematoda: Ancylostomatidae) in Wild Boars (Sus scrofa) in the State of São Paulo, Brazil - Pinto, Michel dos Santos [UNESP]; Neto, João Alfredo Biagi Camargo [UNESP]; de Freitas, Maria Julia Hernandes [UNESP]; Florentino, Bárbara Fuzetto [UNESP]; de Souza Sapatera, Natália [UNESP]; Paiva, Fernando; Nakamura, Alex Akira [UNESP]; Rozza, Daniela Bernadete [UNESP]; Lucheis, Simone Baldini [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (MDPI, 2024)
Although previous studies have characterized the helminth fauna of wild boars kept in captivity in Brazil, records on these helminths in free-ranging animals are still scarce. In view of this, we aimed in our work to investigate the occurrence and morphological and morphometric characteristics of gastrointestinal helminths in wild Sus scrofa from the northwest region of the State of São Paulo, Brazil. The digestive systems of 10 animals (5 males and 5 females of different ages) were used in this study. Each anatomical segment was washed and sieved under running water, and the helminths were separated and identified using light and scanning electron microscopy, according to their morphological characteristics. A total of 2750 (1152 males and 1598 females) nematode specimens were collected from the small intestine of these wild boars, and all of them presented the morphological characteristics of Globocephalus urosubulatus. However, one characteristic is of particular interest because it has not yet been reported in the literature: a marked asymmetry between the lobes and their respective rays of the copulatory bursa, with the left one being larger than the right one. In this research, we identified the presence of G. urosubulatus in all the examined free-ranging wild boars and reported for the first time in the literature the asymmetry in the copulatory bursa.
Keywords: helminths; parasites; swine